1996
DOI: 10.1128/aac.40.11.2605
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-resistant enterococci from nosocomial, community, and animal sources in the United States

Abstract: The presence of vancomycin-resistant enterococci (VRE) was looked for in fecal samples from 104 healthy volunteers (3 with hospital exposure), 100 selected hospitalized patients, and various environmental sources (44 commercial chickens, 5 farm-raised chickens, 3 turkeys, and 2 chicken farm lagoon slurries). Five probiotic preparations were also studied. No VRE with vanA or vanB genes were isolated from the healthy volunteers without hospital exposure, environmental sources, or probiotic preparations. VRE with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
3
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(120 citation statements)
references
References 44 publications
(75 reference statements)
4
101
3
12
Order By: Relevance
“…It has been suggested that enterococcal species with low-level vancomycin resistance (E. gallinarum, E. flavescens, and E. casseliflavus) may usually be present in the microbiota of some birds [37,38]. According to our data, it seems that When only some of the isolates of the group presented the characteristic indicated, the number of isolates with this characteristic is indicated as a superscript E. gallinarum is better adapted to red kites and white storks than to red-legged partridges.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that enterococcal species with low-level vancomycin resistance (E. gallinarum, E. flavescens, and E. casseliflavus) may usually be present in the microbiota of some birds [37,38]. According to our data, it seems that When only some of the isolates of the group presented the characteristic indicated, the number of isolates with this characteristic is indicated as a superscript E. gallinarum is better adapted to red kites and white storks than to red-legged partridges.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] However, in the USA, avoparcin has not been used as an ergotrope, so GRE are not thought to have entered the food chain and colonized the general population. 69 Nevertheless, nosocomial GRE colonization and infection appear to be much more frequent in the USA than in Europe. 70 Alert organism surveillance from routine clinical specimens is the usual method of GRE surveillance in the UK, although a variety of forms of GRE surveillance are undertaken at specific centres.…”
Section: The Epidemiology Of Glycopeptide-resistant Enterococcimentioning
confidence: 99%
“…Over the last few years, intrinsic or acquired resistance of Staphylococcus aureus to many antibiotics, in particular, to β-lactams and glycopeptides has become a major cause of concern. MRSA (methicilin resistant Staphylococcus aureus) causes a health risk, especially in patients with severe underlying disease or immunosuppression (Chadwick et al, 1996;Coque et al, 1996).…”
Section: Introductionmentioning
confidence: 99%